THE EFFECT OF TRANSGLUTAMINASE ON THE RHEOLOGICAL PROPERTIES OF YOGURT - Iuliana Aprodu; Gabriela Gurau; Aurelia Ionescu; Iuliana Banu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of this study was to investigate the rheological characteristics of yogurts obtained from milk treated with transglutaminase prior to fermentation with Streptococus theromophilus and Lactobacillus delbrueckii subsp. Bulgaricus. A set of 36 experiments were carried out to test the influence of various enzyme concentrations ranging from 0 to 0.04%, different setting temperatures (35, 40 and 45 oC), and setting time (60, 90 and 120 min). The cross-linking of milk proteins influenced the post-acidification process as well as the stability of the yogurt samples. The enzymatic treatment of milk allowed avoiding the syneresis phenomena during yogurt storage at 4 oC; the water holding capacity during centrifugation was also improved. Concerning the rheological properties, the apparent viscosity of yogurt increased by increasing the enzyme concentration and the setting time for the entire tested domain of shear rates. The results indicate that transglutaminase catalyzed cross-linking is an effective tool for improving functional properties of yogurt.